Representation of Social Injustice in Capernaum: Cultural and Political Critique in Contemporary Arab Cinema - Ramadhani, Nabila (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Film is one of the most effective media for representing a society’s culture, traditions, and social values. Through film, the identity of a cultural group can be portrayed, both in aspects of daily life and in more complex contexts, such as intercultural interactions. Nadine Labaki’s film *Capernaum* tells the story of Zain, a 12-year-old boy who sues his parents for raising him in abject poverty and for selling his younger sister. This study aims to analyze the forms of representation of injustice as well as the cultural and political critiques contained within the film. This study employs a descriptive qualitative research method using a representational analysis approach. Research data were obtained through observations of scenes, dialogues, and narrative plots found in the film. The findings indicate that the film depicts various forms of social injustice, including extreme poverty, child exploitation, and the marginalization of individuals without legal identity. Furthermore, the film critiques the state’s failure to ensure the protection and well-being of its citizens and highlights the social norms that perpetuate these conditions of injustice. By adopting a realist style and featuring non-professional actors, the film successfully delivers an experience that feels authentic and resonates emotionally with the audience. Therefore, Capernaum can be understood as a powerful representation of social discourse in contemporary Arab cinema, one that not only reflects reality but also fosters critical awareness of humanitarian issues.